Dosimetric comparison of robust angles in carbon-ion radiation therapy for prostate cancer - Shin, Han-Back; Kim, Changhwan; Han, Min Cheol; Hong, Chae-Seon; Park, Seyjoon; Koom, Woong Sub; Kim, Jin Sung (Frontiers in Oncology, 2023)
The objective of this study is to compare the plan robustness at various beam angles. Hence, the influence of the beam angles on robustness and linear energy transfer (LET) was evaluated in gantry-based carbon-ion radiation therapy (CIRT) for prostate cancer. 10 patients with prostate cancer were considered, and a total dose of 51.6 Gy (Relative biolog-ical effectiveness (RBE) was prescribed for the target volume in 12 fractions. Five beam field plans comprising two op-posed fields with different angle pairs were characterized. Further, dose parameters were extracted, and the RBE-weighted dose and LET values for all angle pairs were compared. All plans considering the setup uncertainty sat-isfied the dose regimen. When a parallel beam pair was used for perturbed scenarios to take into account set-up uncer-tainty in the anterior direction, the LET clinical treatment volume (CTV) D95 standard deviation was 1.5 times higher, and the standard deviation of RBE-weighted CTV D95 was 7.9 times higher compared to an oblique pair. The oblique beam fields were superior in terms of dose sparing for the rectum compared to the dose distribution using two conven-tional lateral opposed fields for prostate cancer.